(untitled) (Journal of Engineering, 2018)
In this paper, the time-history responses of a square plan two-story reinforced concrete prototype building, considering the elastic and inelastic behavior of the materials, were studied numerically. ABAQUS software was used in three-dimensional (3D) nonlinear dynamic analysis to predict the inelastic response of the buildings. Concrete Damage Plasticity Model (CDPM) has been used to model the inelastic behavior of the reinforced concrete building under seismic excitation. The input data included geometric information, material properties, and the ground motion. The building structure was designed only for gravity load according to ACI 318 with non-seismically detailing requirements. The prototype building was subjected to El Centro 1940 NS earthquake at different amplitudes (PGA=0.05g, PGA=0.15g, and PGA=0.32g). The elastic and inelastic responses of the 3D numerical model of the same building were evaluated. The differences between the elastic and inelastic displacements and base shear forces were analyzed. It was found from the results that base shear responses are significantly more sensitive to the numerical model of analysis than displacement responses. The evaluation showed that the base shear force and displacement responses of a two-story R.C. building subjected to severe earthquake excitation are very sensitive to the numerical model used whether it is elastic or inelastic.